Characteristics of TCR/CD3 complex CD3ɛ chains of regulatory CD4+ T (Treg) lymphocytes: role in Treg differentiation in vitro and impact on Treg in vivo. Issue 3 (8th November 2013) - Rojo, Jose M; Ojeda, Gloria; Acosta, Yenny Y; Montes-Casado, Maria; Criado, Gabriel; Portolés, Pilar
Abstract : CD4 Treg cells have quantitative and qualitative differences in the TCR/CD3 complex, particularly concerning CD3ɛ chains; differences may reconcile conflicting models of Treg differentiation. ABSTRACT: Tregs are anergic CD4 + CD25 + Foxp3 + T lymphocytes exerting active suppression to control immune and autoimmune responses. However, the factors in TCR recognition underlying Treg differentiation are unclear. Based on our previous data, we hypothesized that Treg TCR/CD3 antigen receptor complexes might differ from those of CD4 + CD25 − Tconv. Expression levels of TCR/CD3, CD3ɛ, ζ chains, or other molecules involved in antigen signaling and the characteristics of CD3ɛ chains were analyzed in thymus or spleen Treg cells from normal mice. Tregs had quantitative and qualitatively distinct TCR/CD3 complexes and CD3ɛ chains. They expressed significantly lower levels of the TCR/CD3 antigen receptor, CD3ɛ chains, TCR-ζ chain, or the CD4 coreceptor than Tconv. Levels of kinases, adaptor molecules involved in TCR signaling, and early downstream activation pathways were also lower in Tregs than in Tconv. Furthermore, TCR/CD3 complexes in Tregs were enriched in CD3ɛ chains conserving their N-terminal, negatively charged amino acid residues; this trait is linked to a higher activation threshold. Transfection of mutant CD3ɛ chains lacking these residues inhibited the differentiation of mature CD4 + Foxp3 − T lymphocytes into CD4 + Foxp3 + Tregs, and differences in CD3ɛ chain recognition by antibodies could be used to enrich for Tregs in vivo. Our results show quantitative and qualitative differences in the TCR/CD3 complex, supporting the hyporesponsive phenotype of Tregs concerning TCR/CD3 signals. These differences might reconcile avidity and flexible threshold models of Treg differentiation and be used to implement therapeutic approaches involving Treg manipulation.